Carbon Monoxide Fate in the Environment as an Inspiration For Biorefinery Industry: A Review - Sobieraj, Karolina; Stegenta-Dąbrowska, Sylwia; Luo, Gang; Koziel, Jacek A.; Białowiec, Andrzej (Frontiers in Environmental Science, 2022)
Carbon monoxide (CO) is ubiquitous in the environment. In this literature review, the biological CO transformations in ecosystems were summarized as an inspiration for biorefinery industry. Specifically, for the first time, information about CO fate in soil, water, and the atmosphere were collected, and CO impact on plants, animals and human was discussed. The review also addresses the need to develop new solutions to implementing circular bioeconomy and highlights the potential of CO use in biologically mediated processes as an untapped valuable resource. Specific key areas of research were identified as (i) development of water-gas shift (WGS) bioreaction, (ii) electricity production during bioelectrochemical syngas conversion (BES), and (iii) electro-fermentation (EF) as a source of added-value biochemicals and fuels.